Association between mutation status and left ventricular reverse remodelling in dilated cardiomyopathy. Issue 21 (17th April 2017) - Dal Ferro, Matteo; Stolfo, Davide; Altinier, Alessandro; Gigli, Marta; Perrieri, Martina; Ramani, Federica; Barbati, Giulia; Pivetta, Alberto; Brun, Francesca; Monserrat, Lorenzo; Giacca, Mauro; Mestroni, Luisa; et al.
Abstract : Objective: To explore the genetic landscape of a well selected dilated cardiomyopathy (DCM) cohort, assessing the possible relation between different genotypes and left ventricular reverse remodelling (LVRR). Methods: A cohort of 152 patients with DCM from the Heart Muscle Disease Registry of Trieste has been studied by next-generation sequencing (NGS). Patients were grouped into different 'gene-clusters' with functionally homogeneous genetic backgrounds. LVRR was defined by left ventricular ejection fraction normalisation or increase ≥10% associated with normalisation in indexed left ventricular end-diastolic diameter or relative decrease ≥10% at 24 months follow-up. Results: A pathogenic disease-related gene variant was identified in 57% of patients: 28 (18%) TTN ; 7 (5%) LMNA ; 16 (11%) structural cytoskeleton Z-disk genes; 9 (6%) desmosomal genes; 18 (12%) motor sarcomeric genes and 9 (6%) other genes. Baseline clinical features were similar throughout the different genotypes. A significant relationship was found between gene cluster subgroups and LVRR, with a lower rate of LVRR in structural cytoskeleton Z-disk gene mutation carriers (1/16 patients, 6%, p<0.05 vs the other subgroups). Of note, structural cytoskeleton Z-disk gene rare variants were independently and inversely associated with LVRR when adjusted for clinical predictors of LVRR (OR 0.065; 95% CI 0.008 to 0.535, p=0.011). Conclusions: NGS confirmed a high genetic diagnostic yield in DCM. A specific 'gene-clusters' classification based on functional similarities in different genes might be helpful in the clinical management of genetically determined DCM. In this study, structural cytoskeleton Z-disk gene rare variants were independently associated with a lower rate of LVRR at follow-up.